Accepting or criticizing religion in the process of globalization - Quoc, Nguyen Anh; Chien, Dinh Van; Dinh, Pham Thi; Toan, Doan Xuan; Chung, Tong Thi Thai; Nghi, Le Viet (Edelweiss Applied Science and Technology, 2024)
Religion, a belief system closely linked to social life, is the subject of research analyzing religious tolerance and criticism in the struggle for human rights. The issue of religious tolerance and criticism will be clarified based on human rights and religious rights. In addition, the relationship between personal ethics and religious ethics is also different, in which the method of combining humanistic philosophy and social philosophy is used to clarify the complex relationships between religion, people, and society, especially the power and role of individuals in religious communities. Research shows that religion influences behavior and shapes people’s value systems and rules of life. However, these value systems sometimes lead to discrimination and conflict. From there, the article concludes that religion is a product of human beings, and its existence can be both a positive and an opposing force in society, depending on specific historical conditions. Studying religious tolerance or criticism is essential to building a harmonious society. People must respect the diversity of beliefs and seek common values in reclaiming human rights in globalization.